(PU)2M2: A potentially underperforming‐aware path usage management mechanism for secure MPTCP‐based multipathing services. (20th June 2017) - Cao, Yuanlong; Song, Fei; Luo, Guoliang; Yi, Yugen; Wang, Wenle; You, Ilsun; Wang, Hao
Summary: Multipath TCP (MPTCP) is a promising transport protocol that allows a multihomed device to simultaneously use multiple network interfaces to send application data over multiple paths. However, although applying MPTCP to data delivery introduces many and attractive benefits, the MPTCP is vulnerable to network attacks. When a path within the MPTCP connection suffers from some types of attacks (eg, a denial‐of‐service attack) and becomes underperforming, it will undoubtedly cause transmission interruption in the stable paths and thus degrade the application‐level performance. Unfortunately, the MPTCP path management mechanism is very simple and cannot timely prevent the usage of underperforming paths in multipath transmission. In this paper, we introduce a new "potentially underperforming" (PU) concept to MPTCP and propose a novel PU‐aware path usage management mechanism (( P U ) 2 M 2 ) for MPTCP aiming to (1) detect and declare an underperforming path and prevent the usage of underperforming paths in multipath transmission, (2) provide a finite‐state‐machine model to change per‐path's state accordingly and effectively manage multiple paths for data transmission, and (3) alleviate the packet reordering problem and make MPTCP avoid throughput performance degradation during network underperforming. We demonstrate the benefits of applying ( P U ) 2 M 2 to MPTCP.